Calidad versus productividad: ¿qué es lo primero? - Vargas, Gustavo A. (Universidad ESAN. ESAN Ediciones, 1993)
This document refers to some key factors as competitive, technological and organizational which may affect management decisions involved in determining the sequence of quality or productivity. The objective is to try to close the "implementation gap" by studying successful experiences (taken from real life) of companies that faced and over sacked this challenge, and by characterizing the internal and external circumstances to the companies that determined the order of priority of the implementation. The analysis has both logical and empirical bases, detailed in the cases described. Finally, the choice will depend between the challenges a company faces, the resources , and the time context in which it has actions. In conclusion, it is possible to define the profile of companies and their internal/external environments that allow to define the order of priority between productivity and quality, for this there are several implementation guidelines: the set of product-market characteristics such as the product lifecycle and the degree of product diversity and market growth rate, cost leadership and immediate access of the product.

Este documento hace referencia a algunos factores clave como competitivos, tecnológicos y organizacionales que pueden afectar las decisiones de gestión involucradas en la determinación de la secuencia de calidad o productividad. El objetivo es intentar cerrar la "brecha de implementación" estudiando experiencias exitosas (tomadas de la vida real) de empresas que enfrentaron y superaron este desafío, y caracterizando las circunstancias internas y externas de las empresas que determinaron el orden de prioridad de la implementación. El análisis tiene bases tanto lógicas como empíricas, detalladas en los casos descritos. Finalmente, la elección dependerá entre los desafíos que enfrenta una empresa, los recursos y el contexto temporal en el que actúa. En conclusión, es posible definir el perfil de las empresas y sus entornos internos/externos que permitan definir el orden de prioridad entre productividad y calidad, para ello existen varios lineamientos de implementación: el conjunto de características producto-mercado como el producto ciclo de vida y el grado de diversidad del producto y tasa de crecimiento del mercado, liderazgo en costos y acceso inmediato al producto.
Keywords: Market growth; Organizational Quality; Crecimiento del mercado; Calidad organizacional; Organizational Productivity; Productividad organizacional; https://purl.org/pe-repo/ocde/ford#5.02.04